Teachers’ attitude towards translanguaging practice and its implication in Indonesian EFL classroom - Raja, Fransiskus Dinang; Suparno, Suparno; Ngadiso, Ngadiso (Indonesian Journal of Applied Linguistics, 2022)
Previous studies have shown that the majority of teachers tend to be receptive towards translanguaging practices (Khairunnisa Lukmana, 2020; McMillan Rivers, 2011; Nambisan, 2014; Yuvayapan, 2019). However, in Indonesian context, there are relatively few studies in this field employing a case study design to reveal more detailed information. This study was aimed at investigating teachers' attitudes towards translanguaging practices and how the practices took place. The participants were four English teachers from two private junior high schools located in East Nusa Tenggara and Central Java, Indonesia. The data were collected by using questionnaires, semi-structured interviews, and observations. The analysis reveals that all participants implemented translanguaging in several typical situations in their EFL classrooms. Despite participants' various feelings towards translanguaging, they still use translanguaging in their teaching and associated translanguaging with positive attributes. Moreover, the majority of teacher participants had positive intentions towards translanguaging in their future class. These findings shed light on a multilingual pedagogical practices and further research directions.Â